Salvage Strategy for Long-Term Central Venous Catheter-Associated Staphylococcus aureus Infections in Children - Alby-Laurent, Fanny; Lambe, Cécile; Ferroni, Agnès; Salvi, Nadège; Lebeaux, David; Le Gouëz, Morgane; Castelle, Martin; Moulin, Florence; Nassif, Xavier; Lortholary, Olivier; Chalumeau, Martin; Toubiana, Julie (Frontiers in Pediatrics, 2019)
Introduction: Current international guidelines strongly recommend catheter removal in case of S. aureus central-line associated bloodstream infection (CLASBI), but a catheter salvage strategy may be considered in children given age-related specificities. No data is available regarding the outcome of this strategy in children. This study aims to evaluate catheter salvage strategy in children with S. aureus CLABSI, and to determine treatment failure rates and associated risk factors. Methods: We retrospectively analyzed data for all children <18 years having a S. aureus CLABSI on a long-term central venous catheter in a tertiary hospital from 2010 to 2014. We defined catheter salvage strategy as a central venous catheter left in place ≥3 days after initiation of empiric treatment for suspected bacteremia, and catheter salvage strategy failure as the persistence or relapse of bacteremia with a S. aureus strain harboring the same antibiotic susceptibility pattern, or the occurrence or the worsening of local or systemic infectious complication between 72 hours and 28 days after the first positive blood culture. Results: During the study period, 49 S. aureus CLABSI on long-term central venous catheter were observed in 41 children (including 59% with long-term parenteral nutrition) and 6 (15%) isolates were resistant to methicillin. A catheter salvage strategy was chosen in 37/49 (76%) cases and failed in 12/37 (32%) cases. Initial presence of bloodstream co-infection, serum concentration of vancomycin under the targeted value and inadequate empiric treatment were significantly associated with catheter salvage therapy failure. Conclusions: Catheter salvage strategy of S. aureus CLABSI on a long-term central venous catheter was frequent in the studied hospital, failed only in one third of cases.